Analisis Thermal Instalasi Capacitor Bank 575 kVar Menggunakan Metode Infrared Thermography - Setiawan, Agus; Suminto, Suminto; Solihin, Lili (Universitas Pamulang, Prodi teknik Elektro, 2024)
The failure of electrical components in the industry can cause production process disruptions, and even accidents. Infrared thermography is an effective method for predictive maintenance, aiming to identify potential component damage before failure occurs. This research aims to analyze the condition of a 575 kVAr capacitor bank installation using infrared thermography. The standard used is the Standard for Infrared Inspection of Electrical Systems and Rotating Equipment. The results of the study indicate that the majority of the 575 kVAr capacitor bank installation conditions fall under priority scale 3, with a maximum temperature of 44.5°C and a delta T of 18.3, which means corrective actions need to be taken with scheduling permission. Corrective actions that can be taken include inspecting cable installations, tightening cable lugs, and tightening terminal connections on contactors and MCCBs. One part that has a priority scale 4 is the MCCB and contactor of the capacitor bank on the lower front section, with a hot point value of 35.1°C and a delta T of 8.9.